Essential of ... global politics - "Langhorne, Richard" (London, 2006)
The arena of global politics is a fast-changing and fascinating one, encompassing as it does the accelerating processes of globalisation, the ever-present threat of war, conflict and terrorism and the role of both key individuals and wider alliances of NGOs and protesters in influencing world events. The Essentials of Global Politics is an essential reference book that guides the reader through these issues and many more, providing an overview of the most important contemporary events and themes. It straightforwardly presents the contextual information required to fully understand the world today, through a combination of maps, lists, key facts and summary information. It offers an accessible discussion of the effects that the processes of globalisation have had on global affairs, within six main sections. Pointers to up-to-date references and websites for further reading and research are provided throughout. Accessibly written and illustrated with useful maps and diagrams, The Essentials of Global Politics will be an indispensable companion for students of politics, international relations and modern history, and a compelling source book for the general reader.
Keywords: Globalization-Political Aspects